2002
DOI: 10.1139/y02-142
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of 1,8-cineole, a terpenoid oxide present in many plant essential oils, in normotensive rats

Abstract: Abstract:The cardiovascular effects of i.v. treatment with 1,8-cineole, a monoterpenic oxide present in many plant essential oils, were investigated in normotensive rats. This study examined (i) whether the autonomic nervous system is involved in the mediation of 1,8-cineole-induced changes in mean aortic pressure (MAP) and heart rate (HR) and (ii) whether the hypotensive effects of 1,8-cineole could result from its vasodilatory effects directly upon vascular smooth muscle. In both pentobarbital-anesthetized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
87
1
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 23 publications
11
87
1
3
Order By: Relevance
“…Its cardiovascular effects were studied by Lahlou et al (2002), using a combined approach in vivo and in vitro. In this research, the authors demonstrated that intravenous administration of eucalyptol significantly reduced the blood pressure of both conscious and anesthetized rats.…”
Section: Eucalyptol (18-cineole)mentioning
confidence: 99%
See 1 more Smart Citation
“…Its cardiovascular effects were studied by Lahlou et al (2002), using a combined approach in vivo and in vitro. In this research, the authors demonstrated that intravenous administration of eucalyptol significantly reduced the blood pressure of both conscious and anesthetized rats.…”
Section: Eucalyptol (18-cineole)mentioning
confidence: 99%
“…This medicinal plant is popularly known as Colony and is widely used by the population as a tea in the treatment of arterial hypertension. Studies have shown that intravenous administration of α-terpinen-4-ol caused immediate blood pressure reduction in a dose-dependent manner in both normotensive (Lahlou et al, 2002) and hypertensive rats (Lahlou et al, 2003). In preparations of isolated rat aorta pre-contracted with depolarizing solution of K + , α-terpinen-4-ol was able to induce a concentrationdependent vasorelaxation (Lahlou et al, 2003).…”
Section: α-Terpinen-4-olmentioning
confidence: 99%
“…Cardiovascular effects were also recently reported. Lahlou et al (11) showed that eucalyptol reduced heart rate by a parasympathetic-dependent action and induced hypotension by a direct vasorelaxation.…”
Section: Introductionmentioning
confidence: 99%
“…1,8-cineole is used in non-prescription pharmaceuticals (e.g. cough suppressant, mouthwash), fragrances and flavoring agents (Lahlou et al, 2002) and can be used as additive to prevent separation in ethanol-gasoline fuel blends (Barton and Tjandra, 1989). Also, it has been shown that 1,8-cineole can be used for the synthesis of p-cymene (Leita et al, 2010;Leita et al, 2011), an important…”
Section: Pathway Construction and Initial Production Of 18-cineolementioning
confidence: 99%